Marketing Strategies to Enhance Consumer Repurchase Interest in Herbal Beverage Products - Nur Muhammad Qolbi; Vembri Aulia Rahmi (Journal of Economic Education and Entrepreneurship Studies, 2024)
This study identifies the strengths, weaknesses, opportunities, and threats faced by the Cap Barokah turmeric and tamarind business and develops strategies to boost consumer repurchase interest. Using phenomenological research with SWOT analysis, data were collected through interviews and field observations to understand internal and external factors influencing consumer behavior. The findings highlight key strengths such as high product quality, hygienic production processes, and competitive pricing. However, weaknesses include limited distribution, lack of halal certification, and minimal use of digital marketing. Opportunities arise from growing public awareness of health benefits linked to herbal drinks and potential product diversification. Conversely, threats include competition from similar products, changing consumer preferences, and economic challenges due to the pandemic. To address these issues, the micro, small, and medium enterprise (MSME) should strengthen its marketing strategy by utilizing digital media, expanding distribution networks, and obtaining halal certification to enhance consumer trust. By leveraging its strengths and opportunities while mitigating weaknesses and threats, the business can foster consumer loyalty and maintain its competitive edge in the local market. Continuous innovation and strategic improvements are essential for achieving sustainable growth in the future.